1999
DOI: 10.1524/zpch.1999.208.part_1_2.107
|View full text |Cite
|
Sign up to set email alerts
|

Copper Electrodeposition on Alkanethiolate Covered Gold Electrodes*

Abstract: We have investigated the structure and thermal dynamics of alkanethiolate layers on Au(lll) with variable temperature scanning tunnelling microscopy (STM), X-ray photoelectron spectroscopy (XPS) and voltammetry. The results build the basis for a study of electrodeposition of copper on alkanethiolate-covered Au(lll). Electrodeposition has been studied as a function of the thiolate chain length, the deposition potential and the temperature. Time-resolved [1][2][3][4][5][6][7].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 91 publications
(54 reference statements)
2
22
0
Order By: Relevance
“…Self-assembled monolayers (SAMs) of aliphatic or aromatic thiols on gold electrodes are frequently employed model systems for a nonconductive surface, onto which a metal has to be deposited. Despite wide-spread usage of proper x-functionalized thiols in order to keep the metal on top of the SAM, common experience in 0039 electrodeposition from solution is the undercreeping of the metal, which finally becomes sandwiched between gold substrate and SAM [11][12][13][14][15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Self-assembled monolayers (SAMs) of aliphatic or aromatic thiols on gold electrodes are frequently employed model systems for a nonconductive surface, onto which a metal has to be deposited. Despite wide-spread usage of proper x-functionalized thiols in order to keep the metal on top of the SAM, common experience in 0039 electrodeposition from solution is the undercreeping of the metal, which finally becomes sandwiched between gold substrate and SAM [11][12][13][14][15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Himmelhaus et al concluded that Hg layers could form between the SAM and Au substrate when exposed to Hg vapor [8]. Copper deposition at SAMs has been studied by various methods [11] including voltammetry [12±14] and scanning tunnelling microscopy [12,13]. They were interested in development of SAMs for stripping voltammetry applications.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous papers dealing with alternative electrodes and techniques have been published recently. Among these, the glassy carbon electrode, 2 graphite electrode, [3][4][5] gold electrode, 6 silver electrode, 7,8 and bismuth electrode 9 are important contributions. But, except for the bismuth electrode, there is a major drawback for these types of electrodes-their use is limited below 2800 mV, restricted by the lack of hydrogen overvoltage.…”
Section: Introductionmentioning
confidence: 99%